Estrategias didácticas activas para fomentar el pensamiento crítico en los estudiantes del segundo semestre de la Carrera de Educación Básica del periodo abril - septiembre 2022 - Lopéz Bravo, Tamara Estefanía (2022)
This research work carries out an analysis of active teaching strategies to promote critical thinking in students, because it favors the performance and development of skills and abilities of students and in this way to acquire knowledge and knowledge. Because an adequate implementation of active didactic strategies has a large part of the commitment of the teacher who is in charge of the learning of the students, he must be able to master and guide in practice everything learned to improve and promote the collaborative learning of young people. of the Basic Education course. However, any activity that helps students improve or encourage critical thinking must be planned and reviewed by teachers, since they are part of the process and thus avoid a lack of effectiveness and commitment on the part of students. In this sense, both teachers and students must in a certain way contribute with the knowledge acquired throughout the academic period by implementing active didactic strategies to strengthen said knowledge. The outcome of this investigative work determined that active teaching strategies are an essential methodology for the learning process, both for students and for teachers of the career. Therefore, it leads us to the result of the implementation of active didactic strategies to strengthen and promote critical thinking in the learning of young people in the second semester of the Basic Education career, helping to increase their reflection, abilities and skills.